Anne of green gables eaudiobook - Montgomery, L. M. (Anne of Green Gables, 2008)
Eleven-year-old Anne Shirley has never known a real home. Since her parents’ deaths, she’s been bounced around to a series of foster homes and orphanages. When she is sent by mistake to live with Matthew and Marilla Cuthbert at the snug white farmhouse called Green Gables, she wants to stay forever. But Anne is not the sturdy boy Matthew and Marilla were expecting. She’s a mischievous, talkative redheaded girl with a fierce temper, who tumbles into one scrape after another. Anne is not like anybody else, the Cuthberts agree; she is special, a girl with an enormous imagination. All she’s ever wanted is to belong somewhere. And the longer she stays at Green Gables, the harder it is for anyone to imagine life without her.